TIMAH HITAM DAN KESEHATAN - Anita Dewi Moelyaningrum (Jurnal Ilmu Kesehatan Masyarakat, 2010)
Lead (Pb) is a heavy metal which is still widely spread in our environment. The source of the lead are industries, fuel with lead, household equipment, cosmetic and also from food. Lead entering the human from inhalation, absorbtion, and skin. Lead compounds indicate that some of the toxic effects for our health. The toxic effects of lead are haemopoitic system, neuron system, urinaria system, gastrointestinal system, cardiofascular system, reproductive system, endocrine system, muskuloskeletal system. The toxicity of lead must be controlled by government to keep the public health.